Primary health care in practice: usual source of care and health system performance across 14 countries - Kevin Croke, PhD; Mosa Moshabela, MMed PhD; Neena R Kapoor, MSc; Svetlana V Doubova, MD DSc; Ezequiel Garcia-Elorrio, MD PhD; Damen HaileMariam, ProfMD PhD; Todd P Lewis, PhD; Gloria N Mfeka-Nkabinde, MD; Sailesh Mohan, ProfMD PhD; Peter Mugo, PhD; Jacinta Nzinga, PhD; Dorairaj Prabhakaran, ProfMD DM; et al. (Elsevier, 2024)
Summary: Primary health care (PHC) is central to attainment of the Sustainable Development Goals, yet comparable cross-country data on key aspects of primary care have not been widely available. This study analysed data from the People's Voice Survey, which was conducted in 2022 and 2023 in 14 countries. We documented usual source of care across countries and examined associations of usual source of care with core PHC services, quality ratings, and health system confidence. We found that 75% of respondents had a usual source of care, and that 40% of respondents accessed usual care in the public sector at primary level. 44% rated their usual source of care as very good or excellent. Access to PHC-linked screenings and treatments varied widely within and across countries. Having any usual source of care was associated with higher take-up of preventive services, greater access to treatment including mental health services, and greater health system endorsement. Strengthening links between health system users and primary care providers could improve take-up of preventive care and increase user satisfaction with health system performance.